Příležitosti k rozvíjení autonomie žáka v hodinách anglického jazyka - Chválová, Marie (Cizí jazyky a jejich didaktiky: teorie, empirie, praxe, 2018)
Title in English: Opportunities for Development of Learner Autonomy in English Lessons This monography deals with the opportunities for development of learner autonomy that teachers provide in their English lessons at lower-secondary schools. The conducted research shows the opportunities that were provided, the nature of observed English lessons with regards to learner autonomy and also teacher beliefs about learner autonomy. Moreover, research findings discuss the connection between teacher beliefs and observed lessons. The monography also describes in detail the creation of a research instrument that can be used for indirect observation of these opportunities in class. The monography points out the importance and diversity of developing learner autonomy and the research results are relevant both for primary and secondary school teachers as well as for university teachers and researchers preparing students for teaching carreer.